The tertiary education sector as a means of development using the example of European micro-nations - Roland Brandtjen (IU Internationale Hochschule, 2024)
Confucius is said to have said; Give a man a fish and you feed him for a day. Teach a man to fish and you feed him for a lifetime. This paper attempts to clarify the impact of the tertiary education sector on sustainable development. For this purpose, 10 autonomous European micro-nations, i.e. the 4 socalled microstates Andorra, Monaco, Liechtenstein and San Marino, as well as the autonomous territories of Guernsey, Jersey, the Faroe Islands, Greenland, the Isle of Man and Gibraltar are used. All have an active tertiary education sector. One wonders why these territories, with few human and economic resources, can afford a rather expensive tertiary education sector. What can we learn from this for other comparable regions? The hypothesis to be tested is that the broader and stronger the tertiary education sector is developed, the more sustainably a society's prosperity grows. The ESCEP analysis, a variant of the PESTLE analysis, is used for this purpose. As an acronym, it includes the consideration of sustainability aspects, such as economic, social, cultural and economic aspects, as well as the political aspect. The paper concludes with a Conclusion, the bibliography and an annex.
Keywords: 650; Micro-nations; SGB 8; tertiary education sector; PESTLE; prosperity growth